A Study on Mobile Hunt App using Android Studio: A Study on Mobile Hunt App using Android Studio - Usharani, B. (Asian Journal of Computer Science Engineering(AJCSE), 2018)
Now a day’s mobile is the major communication tool. Mobile Apps offers information and purpose. Examples for well known mobile apps are SMS, Contact list, calendar, mobile games, Calculator. Mobile Apps do not need internet Connection. Mobile Apps are either free or paid. This paper gives knowledge of how to start working on Android Studio and to develop an app in android studio and get it run on emulator.